A critical review of relationship marketing: Strategies to include community into marketing in development (2011)
An argument for relationship marketing strategies from a community organization approach in a development context is presented in this paper. Emphasis is on the conflict among interests of organizations and interests of individuals, as well as on existent differences with transactional and prescriptive-pecuniary individualistic approach. Because of this, it is proposed that different forms of community organization, through using coalitions, grassroots organization, community leadership, empowerment and other forms of development and community building, must be integrated into relationship marketing. This sets a relationship of organizations with individuals embedded in community.